2015
DOI: 10.1039/c4ra13327g
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-fast rate capability of a symmetric supercapacitor with a hierarchical Co3O4 nanowire/nanoflower hybrid structure in non-aqueous electrolyte

Abstract: A free standing Co3O4 nanowire/nanoflower hybrid structure on flexible carbon fibre cloth (CFC) was designed via a facile hydrothermal approach followed by thermal treatment in air. The Co3O4 hybrid structure on CFC showed interesting electrochemical performance in both alkaline and organic electrolytes when used as electrodes for symmetric supercapacitors. Compared to conventional alkaline electrolytes, the fabricated symmetric cell in organic electrolyte has delivered a high rate and cyclic performance. A su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…This value is much higher compared to the values reported for other all-solid-state symmetric and asymmetric supercapacitors ( Supplementary Information, Table-S4 ). For example, areal capacitance achieved with ANP mr was better than the electrochemical double layer microcapacitors which delivered 0.4–2 mF cm −2 at scan rates of 1–100 mVs −1 27 , and graphene or carbon nanotube based flexible supercapacitors that showed 3–50 mF cm −2 28 . From the prolonged cycle stability performed at the scan rate of 0.6 mA cm −2 , the ANP mr retained ~97% of its initial capacitance even after 5000 consecutive cycles ( Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This value is much higher compared to the values reported for other all-solid-state symmetric and asymmetric supercapacitors ( Supplementary Information, Table-S4 ). For example, areal capacitance achieved with ANP mr was better than the electrochemical double layer microcapacitors which delivered 0.4–2 mF cm −2 at scan rates of 1–100 mVs −1 27 , and graphene or carbon nanotube based flexible supercapacitors that showed 3–50 mF cm −2 28 . From the prolonged cycle stability performed at the scan rate of 0.6 mA cm −2 , the ANP mr retained ~97% of its initial capacitance even after 5000 consecutive cycles ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“… Electrochemical performances of symmetric pseudocapacitors of ANP mr coated on carbon cloth in 3M KOH: ( a ) Typical cyclic voltammogram obtained at a scan rate of 10 mVs −1 ; ( b ) galvanostatic CD profiles of ANPweg at the current density of 10 mA cm −2 ; ( c ) Areal capacitance calculated from CD curves as a function of current density; ( d ) Cycling stability and coulombic efficiency from 5,000 continuous charge-discharge cycles at 10 mA cm −2 ; ( e ) Ragone plot of A ANP mr symmetric supercapacitor compared with other symmetric supercapacitor values reported in literature 27 28 29 ; and ( f ) Nyquist plot of ANP mr symmetric supercapacitor (inset; magnified view). …”
Section: Figurementioning
confidence: 99%
“…Guan et al reported needle‐like Co 3 O 4 /graphene, which can deliver a specific capacitance of 157.7 F g −1 at 0.1 A g −1 in a KOH aqueous solution and keep capacitance retention of 70% after 4000 cycles . By combining flexible carbon fiber cloth and Co 3 O 4 nanowire/nanoflower, Padmanathan et al assembled a symmetric supercapacitor device in an organic electrolyte, which delivered a high cyclic performance and rate capability . These carbonaceous materials may play multiple roles upon composited with Co 3 O 4 used as supercapacitor electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…[25] By combining flexible carbon fiber cloth and Co 3 O 4 nanowire/nanoflower, Padmanathan et al assembled a symmetric supercapacitor device in an organic electrolyte, which delivered a high cyclic performance and rate capability. [26] These carbonaceous materials may play multiple roles upon composited with Co 3 O 4 used as supercapacitor electrodes. On one hand, the electrical conductivity of the Co 3 O 4 -based electrode would be improved to ensure the fast charge transformation.…”
Section: Introductionmentioning
confidence: 99%
“…decorated on carbon textiles as exible electrodes for supercapacitors have been developed. 5,[11][12][13][14][15][16][17][18][19][20] Among various metal oxide electrode materials, NiCo 2 O 4 has been widely researched owing to its high theoretical capacity. 21,22 However, the electrochemical performance of NiCo 2 O 4 -based exible electrode is restricted because of low electrical conductivity of NiCo 2 O 4 .…”
Section: Introductionmentioning
confidence: 99%